Population structure and selective signature of sheep around Tarim Basin - Zhang, Jihu; Zhang, Cheng-long; Tuersuntuohe, Mirenisa; Liu, Shudong (Frontiers in Ecology and Evolution, 2023)
Extreme climate change may lead to a decline in biodiversity and species extinction. And it also results in different population structure and genetic diversity of sheep. Therefore, studying the effects of extreme climate change on the distribution pattern of sheep is of great value. In the long course of evolution, organisms have developed a series of strategies to cope with the harsh natural environment. We used Illumina Ovine SNP 50K BeadChip to study the sheep around in southern Xinjiang of China, living around the Taklimakan Desert. The results showed that a distinct pattern of population structure was observed in 9 sheep breeds and genes related to year-round estrous were obtained by selective gene sweep. The population structure showed that the germplasm resources of all sheep breeds around Tarim Basin were close to each other, which was obviously different from other sheep breeds of other countries. According to the F-statistics, the candidate genes related to year-round estrous were ZO2, IGF1, TSHB and DLG1, and the candidate genes related to sheep reproductive performance were BMP4, LRP8, NF1, and INSL3. This study contributes to a better understanding of the genetic structure and population history of sheep populations in the Taklimakan Desert environment, as well as the regulatory mechanisms of year-round estrous in sheep in the desert environment, which has important implications for the global livestock industry to cope with the challenges of rapidly changing climate and to explore important economic traits.